Antiviral Effects of Heparan Sulfate Analogue‐Modified Two‐Dimensional MXene Nanocomposites on PRRSV and SARS‐CoV‐2. Issue 10 (15th August 2022) - Tong, Ting; Tang, Wantao; Xiao, Shaobo; Liang, Jiangong
Abstract : Due to the worldwide impact of viruses such as SARS‐CoV‐2, researchers have paid extensive attention to antiviral reagents against viruses. Despite extensive research on two‐dimensional (2D) transition metal carbides (MXenes) in the field of biomaterials, their antiviral effects have received little attention. In this work, heparan sulfate analogue (sodium 3‐mercapto‐1‐propanesulfonate, MPS) modified 2D MXene nanocomposites (Ti3 C2 ‐Au‐MPS) for prevention of viral infection are prepared and investigated using severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pseudovirus and porcine reproductive and respiratory syndrome virus (PRRSV) as two model viruses. Ti3 C2 ‐Au‐MPS nanocomposites are shown to possess antiviral properties in the different stages of PRRSV proliferation, such as direct interaction with PRRS virions and inhibiting their adsorption and penetration in the host cell. Additionally, Ti3 C2 ‐Au‐MPS nanocomposites can strongly inhibit the infection of SARS‐CoV‐2 pseudovirus as shown by the contents of its reporter gene GFP and luciferase. These results demonstrate the potential broad‐spectrum antiviral property of Ti3 C2 ‐Au‐MPS nanocomposites against viruses with the receptor of heparin sulfate. This work sheds light on the specific antiviral effects of MXene‐based nanocomposites against viruses and may facilitate further exploration of their antiviral applications. Abstract : Heparan sulfate analogue (sodium 3‐mercaptopropane sulfonate, MPS) modified MXene nanocomposites (Ti3 C2 ‐Au‐MPS) are successfully synthesized, which can strongly inhibit porcine reproductive and respiratory syndrome virus (PRRSV) and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pseudovirus. The results demonstrate the potential broad‐spectrum antiviral property of the as‐prepared Ti3 C2 ‐Au‐MPS nanocomposites against the virus with the receptor of heparin sulfate.